Digital competence and online language teaching: Hong Kong language teacher practices in primary and secondary classrooms. (December 2021) - Wong, Kevin M.; Moorhouse, Benjamin Luke
Abstract: Hong Kong was one of the first public school systems in the world to shift to online learning in response to the COVID-19 pandemic. Primary and secondary school language teachers had to adapt instruction to cater to their students' diverse linguistic and educational needs. Drawing from the European Framework for the Digital Competence of Educators (DCE), the current study examines the experiences of primary and secondary school English language teachers' digital competence as they navigated digital resources, teaching and learning, assessment, and empowering learners in an emergency remote teaching context. Using a two-stage design, this study drew from qualitative survey data ( N = 73) and follow-up interviews ( N = 10). Findings illuminate how language teachers responded to their students' educational and linguistic needs in online environments. Notably, educators adapted their virtual instruction to cater to students with varying English language proficiency levels and leveraged both synchronous and asynchronous platforms to best support student learning. Moreover, the current study sheds light on how the DCE framework might be used as a tool to assess the digital competencies of educators and better prepare them for virtual teaching. It concludes with a call for more research on emergency remote teaching, particularly within primary and secondary language classrooms. Highlights: The current study examines the digital competence of primary and secondary school language teachers in Hong Kong. The study uses a Digital Competencies Framework to understand digital resources, pedagogy, assessments and learners online. Teachers engaged in strategic decision-making about synchronous and asynchronous technologies for instruction. Teachers also reconsidered the purpose and process of lesson preparation, student engagement and assessments. Implications for equipping teachers with digital competence through teacher training and ongoing development are discussed.